"Wag the Dog" initiatives and the corporate immune system. Issue 1 (7th January 2020) - Schweizer, Roger; Lagerström, Katarina
Abstract : Purpose: This paper aims to contribute to the subsidiary initiative literature by studying the interaction between a headquarters and its subsidiary during an initiative process that has the potential to "wag the corporate dog" that is, for the global corporation's promising subsidiary initiative in a strategically important emerging market to question the corporation's prevailing schemata. Design/methodology/approach: The longitudinal single case study draws on evidence from the Indian subsidiary of Swedish Volvo Bus and its efforts to introduce a value product in India. Findings: The study argues that wag the dog initiatives provoke the corporate immune system independent of the initiative's potential and the subsidiary's autonomy and legitimacy. If the idea behind the wag the dog initiative is perceived as strategically important for the multinational corporation, then the corporate immune system tries to engulf – most likely unsuccessfully – the idea within the prevailing schemata. Failed attempts to engulf the initiative weaken the corporate immune system temporarily, thereby opening the organization to revitalization of the original initiative. Resistance, even though weakened, from the corporate immune system continues to exist. Practical implications: Subsidiary managers need to avoid having their headquarters perceive an initiative as a wag the dog initiative by balancing their need to sell persistently the initiative with avoiding negative attention. Originality/value: This study is a pioneer in explaining how the corporate immune system reacts towards wag the dog initiatives taken from subsidiaries in large emerging markets.